A multi-agent RFID-enabled distributed control system for a flexible manufacturing shop - Barenji, Reza Vatankhah; Barenji, Ali Vatankhah; Hashemipour, Majid (Springer London Ltd, 2014)
Flexible manufacturing systems are complex, stochastic environments requiring the development of innovative, intelligent control architectures that support flexibility, agility, and reconfigurability. Distributed manufacturing control system addresses this challenge by introducing an adaptive production control approach supported by the presence of autonomous control units that are cooperating with each other. Most of the currently distributed control systems still suffer from lack of flexibility and agility when the product verity is high and is not reconfigured in case of ad hoc events. To overcome this limitation, a drawback of an excessive dependence on up-to-date information about the products and other elements that move within the system is essential. Radio frequency identification (RFID) is a new emerging technology which uses radio frequency waves to transfer data between a reader and movable item for identification, tracking, and categorization purpose. This paper discusses the architecture devised to deploy RFID-enabled distributed control and monitoring system by means of a set of agents that are responsible for the realization of different control and monitoring tasks and for cooperating to enhance agility, flexibility, and reconfigurability of manufacturing system.
Keywords: RFID; Multi-agent system; Distributed control system; FMS